Percutaneous stent implantation for occluded central shunts in adults: A case report and review of current evidence - Jenab, Yaser; Rezaee, Malihe; Hosseini, Kaveh; Ghaderian, Homa; Haddad, Raymond N.; Zaidi, Ali N. (Frontiers in Cardiovascular Medicine, 2022)
Background Patients with cyanotic complex congenital heart defects (CHDs) commonly undergo palliation with interposition of systemic-to-pulmonary shunts (SPSs). These palliative shunts are rarely found in adults with CHDs and can be complicated with progressive obstruction or total occlusion during follow-up. The best treatment option for shunt re-permeabilization is challenging and case-oriented because most patients are high risk candidates for redo surgeries. We aimed to review the current evidence on percutaneous stent implantation to treat failed SPSs. Methods We performed a comprehensive literature review on percutaneous stent implantation to treat failed and occluded SPSs. We also reported the case of a 33-year-old man with cyanotic CHD and an occluded central aorto-pulmonary shunt, who was successfully treated with percutaneous balloon dilatation and subsequently stent implantation at our institution. Result We identified and included 31 articles reporting on 150 patients and 165 stent implantations in failed SPSs. The age of patients at the time of stent implantation ranged from 6 days to 47 years. The time between the surgical shunt creation and transcatheter intervention ranged from 1 day to 17 years. Overall, 161/165 (97.5%) stent implantations were successful. The most common clinical presentation was cyanosis and decreased atrial oxygen saturations and the indication for stent implantation was shunt obstruction and stenosis. Conclusion This review highlights the benefits of endovascular stenting to permeabilize failed SPSs in children and adults with complex CHD who are classified as poor candidates for re-surgical repair.